Barriers for eco-innovations: A case study of a small firm in Poland - Andrzej H. Jasiński; Filip Tużnik (Foundations of Management, 2013)
This paper is mainly based on a case study of Tuzal Ltd. - a small firm acting in the eco-innovation market in Poland. The main aim of the paper is to analyze main barriers which are being met by enterprises, especially small firms, acting in the eco-innovation market. The following barriers are analysed: problems in convincing customers to innovative solutions; a specific nature of cooperation with local administration units; continuous changes in legal regulations; an increasing market competition; a lack of funds for marketing; a generation gap and a retirement age of the company's owner.
Keywords: 650; eco-innovation; environmental technologies; small firms